IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN SUPPLY CHAIN MANAGEMENT AT PT VITAPHARM - Rachmansyah, Fabbian; Handayani, Wiwik (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The digital era 4.0 has impacted various fields, including technology and education. Rapid advancements in information and communication technology have brought about significant changes in almost all aspects of life. From the widespread use of the internet to the proliferation of interconnected smart devices, everything has transformed culture, economy, and society. This research employs a quantitative descriptive method to describe and analyze phenomena without manipulating variables. The collected data is processed as the basis for this study. This research makes a significant contribution to companies in the implementation of blockchain technology, which has a significant impact on supply chain management. Blockchain enhances transparency and security of transactions through an immutable distributed ledger system, reducing the risk of fraud and increasing trust among transacting parties. Based on data processed using Smart Contracts and blockchain-based applications, this research provides a comprehensive overview of inventory management and calculation. Blockchain technology can integrate and making data transparent, improving the efficiency and effectiveness of company performance. Blockchain theory has been confirmed through real-world implementations, such as the application of blockchain-based applications